Otitis Media and Upper Respiratory Infection Health Loss in 11 Current ASEAN Member States, 1990–2023 - Imanuel Simbolon; Muhammad Rusli; Moon Kaeun (Phlox Institute: Indonesian Medical Research Organization, 2026)
Background: Otitis media and upper respiratory infections (URIs) are distinct Global Burden of Disease (GBD) causes but form a clinically relevant comparative pair for otorhinolaryngology. Objective: To quantify their health loss in 11 current ASEAN member states. Methods: We analysed GBD 2023 estimates for both sexes from 1990 to 2023. Outcomes were all-age disability-adjusted life-year (DALY) numbers, age-standardized DALY rates, and DALY numbers and rates at ages 0–14 years. Country-specific estimated annual percentage changes (EAPCs) used log-linear regression with Newey–West 95% confidence intervals. Analyses were descriptive and non-causal. Results: The sum of 11 national URI DALY point estimates increased from 372,296 in 1990 to 476,741 in 2023 (+28.1%), while the unweighted cross-country median age-standardized rate fell 10.9% to 66.2 per 100,000. Otitis media DALYs increased from 175,399 to 191,971 (+9.4%), while the corresponding median rate fell 19.7% to 29.0 per 100,000. All 22 country-cause EAPC point estimates were negative. Thailand had the highest 2023 URI rate and Cambodia the highest otitis media rate. Ages 0–14 years accounted for 35.8% and 39.1% of summed URI and otitis media DALYs, respectively. Conclusion: Declining standardized rates coexisted with increasing absolute health loss. DALYs provide a planning signal rather than measured clinical workload; translation into otolaryngology services requires local diagnostic, hearing, referral, and capacity data.